Uji Daya Hasil Empat Galur Tomat (Lycopersicum esculentum Mill) di Dataran Rendah - Zakaria '; Adiwirman '; Deviona ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Tomato is one of the leading agricultural commodity that has a good prospect in marketing. It showed by a high demand for this commodity but not balanced with the supply because the productivity is still low especially at the lowland. To overcome this problem, plant breeder must strive to assemble new varieties suitable for cultivation in the lowland. This study aims to examine the growth and yield some tomatoes genotype grown in the lowlands. This study lasted from October 2012 to March 2013 at the experimental farm, Agriculture Faculty, University of Riau. This study arranged experimentally using Randomized Block Design (RBD) consist by 6 treatments and 3 replications. Genotype that used are 2201-5 IPB-8b, IPB-6-8 T43, T53-IPB and IPB 3-3 T65-6. Comparation varieties used are Intan and Karina. The parameters measured were plant height, stem diameter, flowering date, harvesting date, fruit length, fruit diameter, number of fruit cavities, fruit flesh thickness and seed number. The results showed that the strains significantly affect the parameters of the study (flowering date, maturity, plant height, stem diameter, fruit flesh thickness, fruit length, fruit diameter, number of fruit cavities, total fruit weight per plant and number of seeds per gram). IPBT43-6-8 strain has a total weight of fruit cropping highest (777.1 g), but not significantly different from the weight of the total fruit crop IPBT53-3 (655.9 g) and IPBT65-6 (605.5 g). Three strains have a total weight of fruit crop was significantly higher compared with the Intan variety (404.9 g) and Karina (208.6 g). Keywords: tomato, lowland, yield potential evaluation.